Incentives, Supervision, and Sharecropper Productivity - Jacoby, Hanan G.; Mansuri, Ghazala (World Bank, Washington, DC, 2012)
Although sharecropping has long fascinated economists, the determinants of this contractual form are still poorly understood and the debate over the extent of moral hazard is far from settled. The authors address both issues by emphasizing the role of landlord supervision. When tenant effort is observable, but at a cost to the landlord, otherwise identical share-tenants can receive different levels of supervision and have different productivity. Unique data on monitoring frequency collected from sharetenants in rural Pakistan confirm that, controlling for selection, "supervised" tenants are significantly more productive than "unsupervised" ones. Landlords' decisions regarding the intensity of supervision and the type of incentive contract to offer depend importantly on the cost of supervising tenants.